Strategies and Techniques for Quality and Flexibility - Barad, Miryam (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book presents strategic perspectives on quality and flexibility, as well as quantitative tools for assessing their implementation in a range of systems. It introduces readers to the global changes in the relative importance of quality strategies and flexibility strategies over the past 30 to 40 years. In addition, it presents detailed examples of how multi-purpose techniques such as design of experiments, petri nets and quality function deployment can be applied to evaluate quality and flexibility in the design, planning and operation of various systems. Uniquely, the book combines strategies and quantitative research tools in a single volume. It also includes many examples that are accessible to readers from different disciplines, and familiarizes readers with techniques that can facilitate their current and future research - making it a valuable resource for researchers, practitioners and advanced students alike.